My wicked little lies ebook - Alexander, Victoria (Sinful Family Secrets., 2011)
From #1 New York Times bestselling author Victoria Alexander, a captivating new romance in which a daring young woman must choose between her past and her future. . . Evelyn Hadley-Attwater has it all—a genteel Victorian life replete with loving husband, ball gowns and elegant parties. No one, including the man she married, suspects that she was once "Eve," a spy for England's most enigmatic intelligence agency. Summoned for one final assignment, the excitement of her former life and memories of her mysterious, flirtatious boss "Sir" prove too tempting. . . Adrian Hadley-Attwater is a respectable, dignified gentleman. But even the most proper gentlemen have secrets of their own. Secrets from the rest of the world, from their families, from their wives. Secrets that have a price. Now, as a veil of secrecy frays, a tantalizing game of cat and mouse will test the bounds of unfailing love. . . "For love, laughter, and lots of fun, read Victoria Alexander." —Stephanie Laurens, New York Times bestselling author Praise for The Perfect Mistress "Smashing. . .very close to a perfect read." — Publishers Weekly (starred review) "With a delectably dry sense of humor that rivals Oscar Wilde at his best, Alexander fashions the perfect romance, featuring two splendidly matched protagonists engaged in an exceptionally entertaining literary and romantic battle of wills." — Booklist (starred review)